Study on the relationship between the degradation degrees of glutinous rice starch extruded with different α‐amylases and the qualities of Chinese rice wine. (11th March 2022) - Guan, Zhongjing; Zhang, Zhuoyi; Ren, Xiaoru; Bian, Shichao; Xu, Enbo; Jin, Zhengyu; Jiao, Aiquan
SUMMARY: In view that enzymatic extrusion can change the degradation degree of raw materials, this paper studied the regulation rules of four indexes of degradation degree of enzymatically extruded glutinous rice flour and the correlation between these indexes and the quality indexes of brewed Chinese rice wine. The results showed that at appropriate water content, dextrose equivalent (DE) and water solubility index (WSI) were linearly related to the enzyme content in extrusion with thermostable α‐amylase (TS‐αA) and mesophilic α‐amylase (MS‐αA), respectively. But water absorption index (WAI) was not significantly affected by enzyme content. The percentages of each degree of polymerisation (DP) (1–7) and that of the sum of the rest DPs called other DP were the fundamental reasons for different DE values, WSI, WAI and quality indexes of Chinese rice wine. DP1 was significantly positively correlated with alcohol degree, and negatively correlated with total acid. DP2–DP7 (except DP4) was significantly positively correlated with amino acid nitrogen. Besides, other DP was significantly positively correlated with total sugar and total acid. The percentages of DP1, DP2–DP7 and other DP could be respectively adjusted by changing enzyme content in extrusion with MS‐αA, MS‐αA/TS‐αA and TS‐αA to control the related quality indexes of Chinese rice wine. Abstract : The relationship between the degradation degrees of different enzymatic extrudates and the qualities of fermented Chinese rice wine was studied.